PENGARUH EFEKTIVITAS PENGGUNAAN SISTEM INFORMASI TUBERKULOSIS (SITB) TERHADAP KETERSEDIAAN LOGISTIK PADA PUSKESMAS DI KABUPATEN JEMBER - Suhaemi, Iim; Iim Suhaemi, Iim; Rahem, Abdul; Nita, Yunita (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2025)
The Tuberculosis Information System (SITB) is a strategic platform for optimizing TB logistics management in primary health facilities, but its use is still not optimal. This study aims to analyze the effectiveness of SITB usage and its impact on the availability of TB logistics in community health centers in Jember Regency. This study used a cross-sectional design involving 30 community health centers from July to December 2024. Variables examined included technology, management, and organizational components affecting SITB system impact. The effectiveness of SITB was evaluated using the HOT (Human-Organization-Technology) - Fit model, the relationship between components is analyzed using the Spearman rank test. The results show, despite SITB implementation since 2020, logistics availability remained inequitable is still empthy beyond the standard in primary healthcare (> 4%), but Non- antituberculosis logistic have overstocked with an average availability of more than 5 months in quarterly periode (> 150%). Correlation analysis revealed that information quality and user satisfaction significantly influenced system impact (p < 0,05). In conclusion, SITB implementation has not ensured equitable TB logistics availability across community health centers in Jember Regency, where in the used of SITB, information quality and user satisfaction are key factors influencing system impact.